ANUL INTEGRĂRII INFORMAŢIONALE A BIBLIOTECILOR PUBLICE: BILANŢURI - OSOIANU, director adjunct, BNRM, Vera (BIBLIOPOLIS, 2020)
The 23rd edition of last year, of scientific symposium Bibliologic Year was held under the title information integration of public libraries. The national approach to this topic is perfectly justified: the development of information society, information and communication technologies and information resources of public libraries are integrated, and determine the development of new innovative services and the modernization of existing ones. The actuality of the subject is determined by implementation in 2013, of the pilot project Novateca.